The commercial fishery for sharks in the South-Western Cape, with an analysis of the biology of the two principal target species, Callorhinchus Capensis Dumeril and Galeorhinus Galeus Linn - Freer, David Walter Leacroft (Department of Biological Sciences, 2016)
The South African shark fishery began in World War 2, based on a demand for shark liver oil. The initial landings are estimated at 3750 tons per annum, but have since declined to approximately 820 tons of shark, principally Galeorhinus galeus, with an additional 800 tons of Callorhjncbus capensis. The fishery for the later species has largely only developed since 1980. The fisheries for both of the principal species are dependent for their commercial success on fishing schools of breeding aggregations and in both cases the catch is mainly taken in breeding and nursery areas. G. galeus is a largely ichthyophagous species, which forms schools of fish of similar size. After sexual maturity, which is reached at a minimum TL of 1 278 mm (8,5y) for males, and a minimum TL of 1 371 mm (9,9y) for females, these schools further assort to include only mature fish of one sex. They are highly mobile and may be migratory. Fecundity is low in newly sexually mature fish but gradually increases with increasing size, although a mathematical relationship for this could not be established. The maximum number of pups recorded in this study was 20.